BIPOLAR p-degree PERFECT FUZZY MATCHING FOR BIPOLAR FUZZY GRAPHS BASED ON VERTICES (International Journal of Food and Nutritional Sciences, 2022)
A Graph convenient way of representing information involving relationships between objects. The objects are represented by vertices and edges.